Deconstructing the Impact of Entrepreneurship on Income Inequality in Sub-Saharan Africa Countries - Ogede, Jimoh S. (Economics and Business, 2020)
The study examines the impacts of entrepreneurship on income inequality in a panel of 29 Sub-Saharan African countries spanning from 2004 to 2020. The paper employs a dynamic heterogeneous panel approach to differentiate between long-run and short-run impacts of entrepreneurship on income inequality. The findings establish a robust and direct nexus between entrepreneurial activities and income disparity. The results of the two entrepreneurial indicators are stable. Besides, the coefficient of the human capital is positive in the regression and statistically significant at a 5 percent significance level. The proxies for macroeconomic factors exhibit diverse signs and impact, which suggest a policy stimulus aimed at refining macroeconomic situations and also ignite prospects for households to increase their incomes.